2014
DOI: 10.1186/s13058-014-0414-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for self-reported arm lymphedema among female breast cancer survivors: a prospective cohort study

Abstract: IntroductionLymphedema is a potentially debilitating condition that occurs among breast cancer survivors. This study examines the incidence of self-reported lymphedema, timing of lymphedema onset, and associations between sociodemographic, clinical and lifestyle factors and lymphedema risk across racial-ethnic groups using data from a multicenter, multiethnic prospective cohort study of breast cancer survivors, the Health, Eating, Activity and Lifestyle Study.MethodsA total of 666 women diagnosed with breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 47 publications
(78 reference statements)
2
64
1
6
Order By: Relevance
“…In a recent study, Togawa et al showed that a 1.6-fold increased risk of BCRL in AA women was almost entirely eliminated after adjusting for BMI, hypertension, and treatment-related factors [8]. However, in our analyses, controlling for these and other risk factors attenuated but did not completely explain the elevated risk in AA women or with African ancestry.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…In a recent study, Togawa et al showed that a 1.6-fold increased risk of BCRL in AA women was almost entirely eliminated after adjusting for BMI, hypertension, and treatment-related factors [8]. However, in our analyses, controlling for these and other risk factors attenuated but did not completely explain the elevated risk in AA women or with African ancestry.…”
Section: Discussioncontrasting
confidence: 71%
“…Misclassification of BCRL status is certainly possible; however, our analyses excluded any reported BCRL event within the first 6 months of breast cancer diagnosis to minimize misclassification due to postsurgical swelling. Although we assessed self-reported BCRL only up to 48 months after cancer diagnosis, it was recently reported that BCRL incidence primarily occurs within the first five years [8]. While we fully acknowledge that self-report should ideally be validated against physical measures such as perometry, bioimpedance, or arm circumference measures, our proportion of women reporting BCRL was in the range of what has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients are screened for signs and symptoms of BCRL and a clinical exam ensues to confirm a diagnosis. Additionally, those at higher risk of BCRL are more frequently monitored [67]. In order to maximize consistency, the group implemented a well-defined measurement protocol [7].…”
Section: Screening and Preventionmentioning
confidence: 99%